The Effect of Young Coconut Husk on the Quality of Goat Manure-Chicken Excreta Bioculture - Dwi Ahmad Priyadi; Dyah Triasih; Sefri Ton; Ari Istanti (Buletin Peternakan, 2020)
The negative impact of chemical fertilizers use is soil fertility declining. The situation occurs because of biological, physical, and chemical properties of the soil is decreased. Agricultural waste is a large commodity which utilization can still be optimized, for example by using as raw material for organic liquid fertilizer. Agricultural wastes that have good quality as fertilizer include goat manure, chicken excreta, and coconut husk. The utilization of agricultural waste as organic fertilizer is one way of creating sustainable agriculture. This study aims to test the quality of liquid fertilizer (bioculture) of goat manure and chicken excreta by adding various levels of coconut husk. Bioculture is made by anaerobic fermentation for 21 days. The parameters observed included levels of C-organic, N, P, and K bioculture, as well as germination tests to determine the presence of phytotoxins. The data were analyzed using one way ANOVA. The treatment of P5 (5% coconut husk) showed the highest levels of N and P, while the K content was not significantly different from the treatment of P4 (2.5% coconut husk). The germination test showed no phytotoxin activity in bioculture.